Error Analysis on the Concept of Composition of Function in Online Learning from the Perspective of AVAE Categories (ARITH, VAR, AE, and EQS) - Ulfa, Nadia; Jupri, Al; Juandi, Dadang (KnE Social Sciences, 2024)
Algebra is known as a concept that is not only difficult to learn but also difficult to teach properly. Moreover, during the pandemic, learning was carried out online and many studies stated that online learning is not as effective as direct learning (face-to-face). The composition of function is one of the concepts in algebra where errors are often found. This study aims to analyze student errors on the concept of composition of functions in online learning from the perspective of AVAE categories (ARITH, VAR, AE, and EQS). To identify these errors, the researcher used a qualitative research method in which the data collection was done by giving written assignments to 25 high school students of grade X at one of the high schools in Sumedang. Some of the errors that were found in this study include errors in using commutative property, in addition operation (ARITH), students limitations in mastering the various roles of literal symbols (VAR), students not being able to decipher the order in algebraic expressions must be processed (AE), and students make mistakes because they ignore the form of equality in algebra (EQS). These errors that were found in this study can be used as a reference to identify more about learning obstacles that are felt by students which cause them to make errors. Keywords: eror analysis, concept of composition, AVAE categories